Distributed Database Implementation in Point of Sale System with Method Synchronous Replication: (Case Study SBS Endang Buah) - Sri Wulandari; Galuh Son Adji (University of Technology Yogyakarta, 2021)
This SBS Endang Buah is a trading agency that sells various kinds of products fruit. Initially SBS Endang Buah only had one shop with increase in customers then open a branch store to deal with customers which increases. But data that is not distributed quickly result in data delays and make it difficult for the agency to manage sales data at branch stores and central stores. Therefore all data from branches and central stores must be distributed to each other and a base system is made distributed data on the sales system to make it easier for the agency processing sales data. And remembering these data is very important, of course requires data backup to anticipate data loss. Process database distribution will be created in real-time using replication synchronous. Where the master database residing in the central store will be replicated to the branch store slave database and vice versa, replication is carried out in both directions, so that data delays for processing sales data can be resolved as well as with the existence of two databases can anticipate data loss from things technical and non-technical.